Challenges in O-glycan engineering of plants - Strasser, Richard (Frontiers in Plant Science, 2012)
Plants are attractive alternative expression hosts for the production of recombinant proteins. Many therapeutic proteins are glycosylated with N- and O-glycosylation being the most prevalent forms of protein glycosylation. While N-glycans have already been modified in plants towards the formation of homogenous mammalian-type glycoforms with equal or improved biological function compared to mammalian-cell culture produced glycoproteins little attention has been paid to the modification of O-linked glycans. Recently, the first step of mammalian O-glycan biosynthesis has been accomplished in plants. However, as outlined in this short review there are important issues that have to be addressed in the future. These include: (i) elimination of potentially immunogenic or allergenic carbohydrate epitopes containing arabinosides or arabinogalactans. (ii) A detailed investigation of the interplay between engineered N-glycosylation and O-glycosylation pathways to avoid competition for common metabolites like UDP-GlcNAc and (iii) a deeper understanding of signals and mechanisms for distribution of glycan processing enzymes, which is a prerequisite for complete and homogenous glycosylation of recombinant proteins.